Analisis Kinerja Keuangan Pemerintah Provinsi Kalimantan Selatan Tahun Anggaran 2014-2016 - Arfie Yasrie (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
The study was conducted to analyze the financial performance of the local government of Kalimantan Selatan Province in last three years (2014-2016) with a ratio analysis of financial independence, effectiveness and efficiency of the PAD, the ratio of routine expenditure to total expenditure, the ratio of development expenditure to total expenditure, growth ratios, as well as aspects of the analysis financing. Keywords : Financial Performance, Ratio Analysis, APBD, Income, Spending, Financial